Waste management in Slovakia and Poland as European Union member states - Nieścior, Bartosz; Marišová, Eleonóra (Serbian Journal of Management, 2024)
The basic European Union (EU) waste legislation is regulated by European Waste Framework Directive (1975). Since then, this directive has been significantly revised and updated and all EU members are obliged to implement the EU waste legislation into their legislation. The article presents the most important issues related to waste management in Slovakia and Poland. The paper reviews national legislation along with EU legislation. The study includes relevant conclusions with a brief comparison of the analyses carried out. The obtained results  shows that the main goal relating to municipal waste - significant deviation from waste landfilling, set in both states, was not achieved.
Keywords: waste management; European Union; environmental policy; EU member states Slovakia and Poland; sustainable development